Efficient synthesis of α-aminophosphonates using magnetically retrievable ionic nanocatalysts under ultrasound acceleration - Farzaneh Saboury; Najmedin Azizi; Zohreh Mirjafari; Mohammad Mahmoudi Hashemi (Scientific Reports)
Abstract Magnetic supported ionic liquids are a unique subclass of ionic liquids that possess the ability to respond to external magnetic fields, combining the advantageous properties of traditional ILs with this magnetic responsiveness. A novel magnetic ionic nanocatalyst of Fe3O4@SiO2@CPTMS-DTPA was prepared by anchoring an ionic liquid, CPTMS-DTPA, onto the surface of silica-modified Fe3O4. The morphology, chemical structure and magnetic property of the magnetic ionic nanocatalyst structure was characterized using scanning electron microscopy, X-ray powder diffraction, Fourier transformation infrared spectroscopy, vibrating sample magnetometer, and thermogravimetric analysis. The results confirmed the successful attachment of the ionic liquid to the magnetic substrate. Subsequently, the magnetic nanocatalyst was employed for the green synthesis of α-aminophosphonate derivatives. The synthesis was achieved via a one-pot, three-component reaction involving various aldehydes, amines, and different trialkyl(aryl) phosphite derivatives. The reactions were conducted under ultrasound conditions for a duration of 10–25 min, resulting in good to excellent product yields (64–97%). Its recyclability was tested for up to five cycles using magnetic separation which makes it a highly efficient method for quickly separating catalysts from the reaction medium without compromising catalytic activity.